Home/bodies : geographies of self, place, and space - Schissel, Wendy (University of Calgary Press, 2006)
This collection of essays brings together a diverse range of voices that speak to the issues of home, gender, and identity. The essays include information on the ideologies of the human body in the West, the challenges women face in securing the material needs to create healthy homes and bodies, and environments where feminist practices have made a difference.